2004
DOI: 10.1093/hmg/ddh286
|View full text |Cite
|
Sign up to set email alerts
|

A cladistic model of ACE sequence variation with implications for myocardial infarction, Alzheimer disease and obesity

Abstract: Sequence variation in ACE, which encodes angiotensin I converting enzyme, contributes to a large proportion of variability in plasma ACE levels, but the extent to which this impacts upon human disease is unresolved. Most efforts to associate ACE with other heritable traits have involved a single Alu insertion/deletion polymorphism, despite the probable existence of other functional sequence variants with effects that may not be consistently detectable by solely typing the Alu indel. Here, utilizing single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 54 publications
4
36
0
Order By: Relevance
“…Importantly, post-mortem analyses of AD patients determined that those with the I/I genotype had a trend toward increased brain A␤42 load compared with the D/D genotype (25). Single nucleotide polymorphisms in the ACE gene have also been shown to associate with AD, and there is a decrease in the prevalence of the AD-susceptible genotype with increased age, consistent with a modulation of longevity (26).…”
mentioning
confidence: 97%
“…Importantly, post-mortem analyses of AD patients determined that those with the I/I genotype had a trend toward increased brain A␤42 load compared with the D/D genotype (25). Single nucleotide polymorphisms in the ACE gene have also been shown to associate with AD, and there is a decrease in the prevalence of the AD-susceptible genotype with increased age, consistent with a modulation of longevity (26).…”
mentioning
confidence: 97%
“…Meta-analysis based on a large number of studies has indicated that the D allele that confers increased ACE levels may not be clinically relevant in the general population but may play a role in specific subgroups of individuals (28). Recently, the use of platforms that enable simultaneous test of multiple single nucleotide polymorphisms (SNPs) per locus has provided additional evidence for positive associations between ACE and metabolic or vascular phenotypes, indicating that under certain conditions or genetic backgrounds the ACE locus may play a role (13). Altogether, these data highlight the difficulties in assessing the contribution of single factors to a complex phenotype.…”
mentioning
confidence: 99%
“…We found no differences for SNPs rs4343 or rs1800764 for BMI between any case and control grouping, in contrast to the earlier finding reported in a subset of Swedish male patients. 26 In the diploclade analysis, the only significant P-value result was for the AA diplocladotype in male children, which was not significant if any correction for multiple testing was made. This association in children is also opposite to that reported by the Italian I/D study, which found an age effect in the deletion carrying individuals, as the diploclade AA represents homozygosity for the insertion carrying allele.…”
Section: Discussionmentioning
confidence: 92%
“…Linkage disequilibrium was calculated using HaploXT from the result for all cases and controls and graphically displayed using the programme GOLD. 38 The common clades were inferred using the method of Katzov et al 26 This involved using the genotypes for rs1800764 and rs4343 to assign the possible cladotypes A, B, and C. These are genotypes (for rs1800764 followed by rs4343) of TA, CG, and TG for the respective clades A, B and C. Processing the data from these two SNPs with PHASE v2.1 was used to infer the clades. 37 Diploclades, that is, the clades assigned to the two chromosomes for each individual, were then assigned based on the determined clades.…”
Section: Statisticsmentioning
confidence: 99%
See 1 more Smart Citation